Study of Metal–Dielectric Interface for Improving Electrical Properties and Reliability of DRAM Capacitor - Lim, Han Jin; Choi, Jae Hyoung; Cho, Gihee; Chang, Jaewan; Kim, Younsoo; Jung, Hyung Suk; Shin, Kyoung Sub; Seo, Hyungtak; Jeon, Hyeongtag (Advanced Materials Technologies, 2023)
The interface between a dielectric thin film and a metal electrode is studied to improve reliability as well as electrical properties of the metal–insulator–metal (MIM) capacitor in dynamic random-access memory (DRAM) devices. The interfacial layers between a dielectric thin film and a metal electrode play important functional roles such as increasing the electrical barrier or preventing oxygen defects in high-k dielectrics. By introducing an electrical barrier layer or a sacrificial layer at the metal–dielectric interface for engineering the electronic band, lattice, or dipole, various effects could be confirmed such as the conduction band offset (CBO), bandgap or mismatch modulation for controlling the dielectric loss depending on the AC frequency or leakage current of MIM capacitors. Upon the insertion of Al2O3 as an electrical barrier layer, CBO increased because of the band engineering. Further, upon the insertion of TiO2 as a sacrificial layer at the interface, CBO increased because of the dipole formation at the interface, attributed to the difference in electronegativity. Thus, a robust MIM capacitor for DRAM that maintains a low leakage current and has improved reliability which is realized using the proper combination of interfacial layers.
Keywords: Conduction band offset; Dielectric thin films; Dynamic random access memory; Electronic band structure; High- k; Metal capacitors; Metal electrodes; Metal insulator metals; Metal-dielectric interface; Metal–insulator–metal capacitor; DRAMs; electronic band structures; high-k; MIM capacitors